Eicosanoids in Invertebrate Signal Transduction Systems. - Stanley, David W. (David Warren), 1946- (Princeton legacy library., 2014)
This volume generates a new paradigm for researching and understanding the biological meaning of eicosanoids. Eicosanoid is a general term for oxygenated metabolites of certain polyunsaturated fatty acids. The compounds are extremely important in human biology, in which they are well understood. Their importance to humans, however, has tended to overshadow their broader biological significance. David Stanley seeks to change that in this book, providing a general sketch of the medical background on eicosanoids and then developing a detailed critical treatment of eicosanoid actions in inverte.